Implementing blended learning in higher education - Lasić-Lazić, Jadranka; Mateljan, Vladimir; Banek Zorica, Mihaela Pavlina, Krešimir (2006)
The implementation of blended learning at the Faculty of Philosophy in Zagreb proved so far that combination of e-learning and classical face-to-face classroom teaching can be successful. Positive feedback has been received from the focus groups. Students are very satisfied with implementation of blended learning because it gives them both flexibility and convenience. They emphasized the importance of on-line communication for support and guidance from the teacher. Blended learning can help both teachers and students to automate some administrative tasks (such are attendance records and assignments) while keeping face-to-face contact which is very important motivational factor in education.
Projekt MZOS
ENG